De remédio à bebida da felicidade: sociedade hedonista através das propagandas da Coca-Cola - Matias, Milenne Ferreira de Sousa (2015)
The consequences of modernity led to great social changes that affected the composition of cultures, which brought about transformations of traditions, community ties and, consequently, the transmission of memory. The present work proposes to understand the social time in which we are inserted, analyzing the advertisements of Coca-Cola from the period of 1886 to 2015, with a representative sample on the main themes addressed in its campaigns throughout its history. The hypothesis that guided the present work is that the social time in which we live is not repressive - that compels individuals to dull autonomy - but rather hedonic, defined by the ideal of happy life, guided by the "pleasure principle" and the "Orgasmic experience" (Zigmund Bauman) as the analytical category of social behavior (PIRES).